Agriculture and climate change: The potential for soil carbon sequestration - Lal, Rattan (International Food Policy Research Institute, 2009)
Of the five principal global carbon pools, the ocean pool is the largest at 38.4 trillion metric tons (mt) in the surface layer, followed by the fossil fuels (4.13 trillion mt), soils (2.5 trillion mt to a depth of one meter), biotic (620 billion mt), and atmospheric pools (800 billion mt). If the fluxes among terrestrial pools are combined, annual total carbon flows across the pools average around 60 billion mt, with managed ecosystems (croplands, grazing lands, and plantations) accounting for 57 percent of that total. Thus, land managers have custody of more annual carbon flows than any other group.